Expressão do gene da leptina em cultura de células de camundongos ob/ob como modelo para síndrome do ovário policístico - Parreira, Rafael Martins [UNIFESP] (2014)
The polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and affects 15 to 20% of patients with infertility. PCOS shows reproductive implications, endocrine, dermatological, gynecological, cardiac and psychological with symptoms ranging from infertility due to ovulatory dysfunction, menstrual disorders and / or androgenismo signals. Furthermore, obesity affects the majority of women with PCOS and therefore many studies have been done to relate obesity and infertility in women with PCOS. The weight loss can improve the levels of androgens and glucose, as well as ovulation and pregnancy rates. It is known that the energy balance in mice is regulated by the ob gene which expresses the leptin. This protein acts in adipose tissue by regulating the size of the body fat deposit, and play a role in reproduction, including a direct effect on the ovary. With advances in molecular biology techniques and the emergence of gene therapy as a new form of treatment, this study aims to verify the potential of gene therapy using the leptin gene in ob mice cells / ob as a model for PCOS. mouse cells ob / ob began to express the leptin gene after transfection. The expression levels of leptin in the transfected cells, both ob / ob and the control were significantly higher and above the baseline level. Given these results, there is the need for future in vivo studies for further treatment associated gene therapy and cell therapy in patients with infertility related to PCOS